2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24091
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Team Processes in Virtual Team Projects Through a Web-Based Collaboration Tool and Instructional Scaffolds

Abstract: Because of the global nature of the workforce, teams are becoming increasingly distributed and virtual. These teams typically use a variety of web-based information and communication technologies (ICT) to collaborate from remote locations. Although there has been increased emphasis on developing teamwork skills and abilities in engineering students through the use of collaborative projects, our understanding of successful strategies to enhance learning outcomes in these distributed settings is lacking. There h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The learning occurred through knowledge exchange (e.g., engineering students explained basic engineering or science concepts and PSTs shared approaches to engage student audiences), collaborative problem solving (e.g., groups work together to identify a viable design problem), communication, and teamwork (Hirsch et al, 2001). The interdisciplinary partnership used a scaffolded approach to collaboration that has been validated and successfully implemented in prior research (Pazos & Magpili, 2015;Pazos et al, 2016;Pazos et al, 2019). Students learned through creating and delivering engineering content while receiving periodic feedback and reflecting on and revising their content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The learning occurred through knowledge exchange (e.g., engineering students explained basic engineering or science concepts and PSTs shared approaches to engage student audiences), collaborative problem solving (e.g., groups work together to identify a viable design problem), communication, and teamwork (Hirsch et al, 2001). The interdisciplinary partnership used a scaffolded approach to collaboration that has been validated and successfully implemented in prior research (Pazos & Magpili, 2015;Pazos et al, 2016;Pazos et al, 2019). Students learned through creating and delivering engineering content while receiving periodic feedback and reflecting on and revising their content.…”
Section: Discussionmentioning
confidence: 99%
“…SCOL was selected because of its evidence of success in promoting effective teamwork, ease of use, ability to tailor to specific course projects, and broad and free availability in most universities. SCOL incorporates scaffolds in the form of group activities, tasks, and templates that have been thoroughly tested and are built on evidence-based best practices in teamwork (Pazos & Magpili, 2015;Pazos et al, 2016;Pazos et al, 2019). The scaffolds are used to provide direction and structure for critical collaborative processes (planning, role assignment, progress tracking, and feedback) and guide the lesson development process.…”
Section: Introductionmentioning
confidence: 99%
“…17 Two prior empirical studies support the effectiveness of the intervention (scaffolds) by empirically showing that a combination of the collaboration tool and embedded scaffolds have significant impact on teamwork skill development for engineering students. 18 We extend this study by exploring qualitatively how the scaffolds supported collaborative work and what elements of the intervention made an impact to the different processes that teams go through when working in projects.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…The first stage of the study looked into the impact of the intervention from a hypothetical deductive perspective and showed evidence of the positive impact of the collaboration tool and embedded scaffolds. 18 The study reported here is the second stage qualitative analysis that explores how the intervention (collaboration tool and scaffolds) are used to support different team processes as well as factors that affect this.…”
Section: Transition Processesmentioning
confidence: 99%
“…One of the primary outcomes for the engineering education is to train students for conducting engineering design and be a better fit for the industrial needs 1,2 . The accelerating pace of the globalization of design makes long-distance communication and project management necessary skill sets for engineers since many companies now operate internationally.…”
Section: Introductionmentioning
confidence: 99%